The awareness of Muslim consumers towards the halal logo in Malaysia - Abdul Razif Zaini; Yoyo, Yoyo (Penerbit Universiti Kebangsaan Malaysia, 2021)
The halal logo is an important symbol for the Muslim community in Malaysia and around the world. The logo is the standard for consumers in determining the halal status. It is one of the important instruments for consumers in choosing food and restaurant premises as a dining destination. Although the logo is a positive development for Muslims in Malaysia, this scenario has caused the Muslim community to put their full reliance on this logo in the selection of restaurants. The level of knowledge in determining the halal status is low. The community lacks the ability to determine the legitimacy of food because of the high degree of dependence on the logo. Therefore, this study aims of explaining the concept of halal logo use, identifying consumer awareness of the use of halal logo and assessing the level of dependence of Muslim users on the halal logo. The design of the study was the observation-based survey. Participation observation is conducted to critically examine, view and review situations or events based on the objectives established. Unstructured observation is made without referring to a set of activities or aspects that have been identified specifically. However, this observation is guided by a checklist for data collection focused and meets the objectives set. Observations were made on food premises located at one of the major shopping malls in the Klang Valley. The findings are expected to assess the extent to which consumers have been exposed to the use of halal logos in food establishments in Malaysia.